(3JfRjg GdTQjYI GdeQahYI Yf GdCNHGQ GdTfjYI GdehVhYIs - (3Ydj Hf eMeO Hf Ydj Hf YHO GdQMef GHf YQGb GdcfGfj, fhQ GdOjf,J (B963 (3g` s
(3ChdgG (B:s
(3hHYO aEf ef GdegeGJ Yf Cgd GdYde hGdJbi eYQaI GdCMGOjK GdehVhYI Ydi SjO GdoeQSdjf dJJbi s
(3BNQgG (B:s
(3hMOjK ef cSQI dHkG aYdjg LHQg bGd eDdag YaG Gddg Yfg gfG GfJgi HGdZQV GdPj CQOfGg ef LeY eG aj cJH GdMGaXjf GHf GdLhRj hGdSjhWj hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B218s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B494s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs